WHAT ARE THE CAUSES AND EFFECTS OF SOCIAL MEDIA ADDICTION? - Ahmedov Azimjon Ilhomovich the teacher of Andijan State Institute of Foreign Languages; ABDUQAXOROVA MALIKAXON , NUMONJONOVA GULNOZA student of Andijan State Institute of Foreign Languages, 312-group – English language; literature (ZAMONAVIY TA’LIMDA FAN VA INNOVATSION TADQIQOTLAR, 2023)
This article about that social media is addictive because it activates the reward centers in the brain, a mechanism also seen in substance use disorders.